Streptococcus agalactiae is resistant to β-lactam antibiotics in a diabetic patient with foot infection: a case report - Yolanda Pitra Kusumadewi; Afdina Melya Ganes Febiyanti; Ilma Tazkiya; Galang Ridha Allatief; Annisa Somaningtyas; Cicilia Widhi Astuti; Ika Puspitasari; Kuwat Triyana; Tri Wibawa; Titik Nuryastuti (Journal of Clinical Microbiology and Infectious Diseases, 2022)
Introduction: Diabetic foot infection is a complication that often occurs in people with diabetes mellitus. Staphylococcus aureus is the most common microorganism found in diabetic foot infections. In addition, coagulase-negative staphylococci, Enterococcus faecalis, Streptococcus agalactiae, and Pseudomonas aeruginosa can also be demonstrated. Diabetic foot infection treatment usually takes a long time which may increasing the risk of antibiotic resistance. This article will present a unique and interesting case about Streptococcus agalactiae resistant to β-lactam infection. Case description: A 56-year-old man presented with a long history of diabetes mellitus but had not taken anti-diabetic drugs and had no history of previous use of antibiotics. Since 2016 his right foot had a recurring wound that he routinely treated. Microbiology culture of the wound swab obtained three bacteria namely Streptococcus agalactiae, Proteus mirabilis and Klebsiella pneumoniae which is resistant to β-lactam antibiotics. Conclusion: The identification of Group B Streptococcus bacteria (Streptococcus agalactiae) which are resistant to β-lactam antibiotics (penicillin, third and fourth generation cephalosporins) which were found in this case, reminds all medical personnel to be more careful and prudent in the rational use of antibiotics.